Heterotopic pancreas in the gastrointestinal tract in children: a single-center experience and a review of the literature - Giorgio Persano; Noemi Cantone; Elisa Pani; Enrico Ciardini; Bruno Noccioli (BMC, 2019)
Abstract Background Heterotopic pancreas, that is the abnormal localization of a well-differentiated pancreatic tissue, is a rare occurrence in pediatric patients. Most lesions are found incidentally; in some circumstances, the presence of heterotopic pancreas may cause gastrointestinal symptoms, such as obstructive symptoms or bleeding. Patients and methods The clinical notes of patients with histological diagnosis of heterotopic pancreas treated at Meyer Children's Hospital between 2009 and 2017 have been retrospectively examined. Four variables have been examined: clinical presentation, age at diagnosis, timing of surgery and localization of the heterotopic pancreas. Patients have been classified accordingly. Results Fourteen patients were diagnosed with heterotopic pancreas at a single institution. In half cases, heterotopic pancreas caused symptoms that warranted surgical exploration. Symptomatic patients were significantly older than patients in whom heterotopic pancreas was an incidental finding (mean age 9 years and 5 months vs 2 years and 9 months; p = 0.02). Heterotopic pancreas was more frequently found in patients who underwent urgent surgical procedure than in patients who underwent elective surgery (2.61% vs 0.22%; p < 0.0001). In all cases, foci of heterotopic pancreas were resected. Conclusion Heterotopic pancreas is usually discovered in the submucosa of the stomach, duodenum and small bowel. Heterotopic tissue may cause symptoms related to mechanical complications, bleeding from the surrounding intestinal mucosa or, occasionally, to the development of malignancy. Heterotopic tissue is a rare but clinically relevant cause of gastrointestinal symptoms. The presence of heterotopic tissue should be considered in children with gastrointestinal symptoms of unclear origin and surgical resection is advisable.